PERMAINAN EDUKATIF UNTUK ANAK USIA DINI - Angga Saputra (Program Studi Pendidikan Islam Anak Usia Dini - IAI Muhammadiyah Bima, 2019)
This article is entitled: Permanan Educative Early Childhood. With the aim is to know educational games for early childhood. Educational games for early childhood, playing is one of the words that are quite familiar to our ears, especially if we become a teacher, especially for PAUD teachers. Game tools are all tools used by children to fulfill their instincts of play. The game tools in question are for example soccer ballsfrom plastic cars, calluses, pistols, puppets, imitation of cooking tools and so on. So the educational game tool is all the game tools that children useto fulfill their instincts of play. So early childhood educational games are games that can meet the needs of children’s play instincts.